Introduction To Public Relations - IM93 - 202302 - Mackelmann Roedenbeck, Mathias (2023)
This course is designed to offer students an overview of public relations from a communication perspective. The course is designed to develop in students a broad understanding of public relations ¿ what it encompasses, its history and influences, and its practices and processes in the contemporary business world and in society at large. Ethical issues for public relations practitioners will be considered, as well as the impact of globalization and new technologies in this field, through examination of current events and case studies. Students are expected to ask questions, respond to lectures and actively participate in all discussions. Lectures will expand on the material covered in the online textbook. Course objectives: ¿ Understand what public relations is and be able to identify it in the world around you ¿ Understand and apply communication strategies and theories to achieve organizational goals ¿ Be able to identify and describe an organization's key publics ¿ Be able to implement the public relations process in developing strategic PR plans ¿ Know how to use PR tactics - written, spoken and visual - including new technologies ¿ Understand the ethical implications of public relations practice Expected Learning Outcomes ¿ Demonstrate knowledge of the role and value of the public relations discipline and profession ¿ Identify the processes involved in the 4-Step Process: Research, Planning, Communication/Implementation, Evaluation ¿ Demonstrate knowledge of how technology and globalization have in part shaped the PR industry ¿ Demonstrate knowledge of how the PR industry influences the media ¿ Demonstrate an understanding of the role of ethics for the PR practitioner, the profession, the organization and its constituents, and the greater community 1¿ Identify and differentiate career opportunities within the area of strategic communication ¿ Identify and describe an organization¿s key publics ¿ Differentiate the major theories in the field of communication and public relations to achieve organizational goals in public relations activities ¿ Produce effective messages supported by research